Performance Evaluation of AML Equipment for Determining the Depth and Location of Subsurface Facilities in South Korea - Seung-Jun Lee; Hong-Sik Yun (Applied Sciences)
The accurate detection and mapping of subsurface utilities are critical for ensuring safety and efficiency in excavation and construction projects. Among various technologies, Ground-Penetrating Radar (GPR) has been widely used for locating underground infrastructure due to its non-destructive nature and ability to detect both metallic and non-metallic materials. However, many GPR systems struggle to meet the practical depth requirements in real-world conditions, especially when identifying non-metallic facilities such as PVC and PE pipes. In South Korea, the legal regulations require underground utility locators to meet specific accuracy standards, including a minimum detectable depth of 3 m. These regulations also mandate periodic performance testing of surveying equipment at authorized inspection centers. Despite this, most GPR systems tested at the official performance evaluation site at Sungkyunkwan University demonstrated limited effectiveness, with an average detection range of only 1.5 m. This study evaluates the performance of a handheld All Materials Locator (AML) device developed by SubSurface Instruments, Inc., (Janesville, WI, USA) which uses ultra-high radio frequencies to detect subsurface density variations. Experimental results from both the certified test facility and field conditions indicate that the AML meets South Korea’s legal requirements for minimum depth and accuracy, by successfully identifying a wide range of subsurface utilities including non-metallic materials. The findings suggest that the AML is a viable alternative to conventional GPR systems for utility detection in regulated environments.